2022
DOI: 10.1016/j.biopha.2022.112650
|View full text |Cite
|
Sign up to set email alerts
|

Reactogenicity and immunogenicity of heterologous prime-boost immunization with COVID-19 vaccine

Abstract: Background The objective of the present work was to assess the reactogenicity and immunogenicity of heterologous COVID-19 vaccination regimens in clinical trials and observational studies. Methods PubMed, Cochrane Library, Embase, MedRxiv, BioRxiv databases were searched in September 29, 2021. The PRISMA instruction for systemic review was followed. Two reviewers independently selected the studies, extracted the data and assessed risk of bias. The quality of studies was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 51 publications
4
26
1
Order By: Relevance
“…Homologous or heterologous COVID-19 prime-boost vaccinations are introduced and reported to improve the humoral and cellular immune responses [ 6 , 7 ]. A homologous third dose of CoronaVac demonstrated increased immune responses against SARS-CoV-2; however, immunogenicity was lower when compared to a heterologous prime-boost with BNT162b2 [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Homologous or heterologous COVID-19 prime-boost vaccinations are introduced and reported to improve the humoral and cellular immune responses [ 6 , 7 ]. A homologous third dose of CoronaVac demonstrated increased immune responses against SARS-CoV-2; however, immunogenicity was lower when compared to a heterologous prime-boost with BNT162b2 [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of clinical trials and observational studies have suggested that a heterologous vaccine booster dose (e.g., using the mRNA vaccine after a primary vaccination scheme based on the adenoviral vector vaccine) is generally well-tolerated. Moreover, they evoke robust immunity and, in some cases, may offer additional benefits in terms of greater humoral and T-cell response and, subsequently, higher effectiveness [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The data on the reactogenicity of heterologous booster vaccinations compared to homologous schedules are limited. However, some previous studies have shown that receiving the mRNA vaccine after the first dose of adenoviral vector vaccine, or vice versa, may lead to a higher frequency of side effects, mostly mild or moderate, and resolving within 1–3 days [ 16 , 18 , 19 , 20 ]. Some initial observations also indicate that those who receive a heterologous booster dose, regardless of the combination of vaccine types, can expect greater reactogenicity [ 14 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, no case of thrombocytopenia appeared among the examined cases. This study revealed that heterogeneous vaccination could have short-term disadvantages, and further studies are needed to determine their safety [ 91 , 92 ].…”
Section: Potential Mixing Matching Sars-cov-2 Doses and Booster Vaccinesmentioning
confidence: 99%
“…The third shot or booster shots may improve the protection against severe disease symptoms [ 97 , 98 ]. Booster shots are usually given after 5–6 months, followed by the second vaccination [ 92 , 99 ]. A booster shot may be needed to maintain protection against virus-related disease.…”
Section: Potential Mixing Matching Sars-cov-2 Doses and Booster Vaccinesmentioning
confidence: 99%